REVIEW OF MULTIPLE INTELLIGENCE IN ISLAMIC RELIGIOUS EDUCATION LEARNING: STRATEGY AND IMPLEMENTATION IN PESANTREN - Riky Supratama; Husna Nashihin; Ridho Muttaqin; J Joni; Triana Hermawati (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to examine the extent to which the methods and applications of the theory of multiple intelligence are in harmony with the perspective of Islamic education. The foundation of this study refers to the concept of compound intelligence developed by Howard Gardner. The main focus of this research is the strategy and application of the theory of multiple intelligence in the learning process of Islamic Religious Education in the pesantren environment. This study uses a qualitative approach with data collection techniques through observation, interviews, and data analysis based on the Miles and Huberman model. The results of this study are expected to provide a more comprehensive insight into how the theory of multiple intelligences can be applied in Islamic religious learning. In addition, this research also aims to dig deeper into how this concept can optimize the cognitive and emotional potential of every student in the Islamic education system.